Introduction: Fertility and Social Inequalities in Migrant Populations: a Look at the Roles of Selection, Context of Reception, and Employment - Nadja Milewski; Alicia Adserà (Journal of International Migration and Integration, 2022)
This paper is the introduction to the Special Issue on "Fertility and social inequalities in migrant populations." The Special Issue contains twelve empirical papers that deal with both international migrants and internal migrants, both women and men, both older migrant populations spanning several generations as well as recent immigrant groups, such as refugees, and include analyses of both behavior and intentions. The data used comprise macro indicators and individual-level data as well as qualitative material. Regional contexts include classical immigration countries in Europe and Oceania as well as relatively recent destinations. The papers draw on several comparative perspectives—migrants at destination, emigrants and stayers at origin, migrants with different numbers of children upon migration, and different migrant generations—to address three large questions. Six papers explore the role of time and sequencing in migrant fertility, in relation to both period effects and sequencing of births in the life course, as well as the role selection into migration plays in female and male migrants' fertility behavior. Four papers focus into how regional variation in the receiving contexts shapes fertility behavior, highlighting the role of migrant type, human capital, and social capital. Two papers look at how childbearing is associated with different degrees of economic assimilation, i.e., maternal employment. Overall, this Special Issue demonstrates the large heterogeneity in fertility among migrant and ethnic minority groups. Social inequalities shape fertility differentials, which in turn influence subsequent life courses of migrants and ethnic minority group members. Future research on migrant assimilation should pay more attention to variation in demographic behavior.
Keywords: 300; Migrants; Fertility; Demographic behavior; Maternal employment; Selection; Heterogeneity